Neurological complications of diabetes mellitus - O. V. Kotova; E. S. Akarachkova; A. A. Belyaev (Медицинский совет, 2019)
Diabetes mellitus (DM) seriously and negatively affects the physical, mental and social well-being of patients. Among the complications of DM, neurological complications associated with both central and peripheral nervous system lesions are of great importance to the patient’s health. These include reduced cognitive function and neuropathy. A decrease in cognitive function associated with DM is observed in both patients with DM 1 and 2 types. There is a connection between the presence of diabetic retinopathy at baseline and changes in cognitive function over time in patients with DM2. Initial diabetic retinopathy and the severity of retinopathy are associated with a decrease in all cognitive functions and a decrease in the rate of information processing. The pathogenesis of diabetic polyneuropathy (DPN) is determined by metabolic disturbances in nerve and epithelial cells, which occur due to hyperglycemia and lead to impaired function of microcirculatory vessels and peripheral nerve fibers. Pathogenetic treatment of DPN is based on modern ideas about the mechanisms of its occurrence and progression. In particular, preparations with antioxidant effect are used, among which the efficacy of alpha-lipoic (thioctic) acid (ALA) in DPN is well proven, and one of such preparations is Berlithion («Berlin-Chemie», Germany). Among other effective drugs used in the treatment of neurological complications of DM, dipyridamole (Curantyl) is used, as the drug affects microangiopathy associated with DM.